Assessing the Effectiveness of Telemedicine for Cervical Cancer Screening in Remote Areas of Indonesia - Kristianti, Silvia; Reza Andrianto; Sonya Syarifah; Taryudi Suharyana (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
Introduction: Cervical cancer remains a significant public health issue in Indonesia, particularly in remote areas with limited access to healthcare facilities. Telemedicine offers a potential solution to overcome geographical barriers and improve cervical cancer screening rates. This study aimed to assess the effectiveness of a telemedicine-based cervical cancer screening program in remote areas of Indonesia. Methods: A cross-sectional study was conducted in five remote villages in Indonesia. Women aged 30-49 years were invited to participate in cervical cancer screening using a telemedicine platform. The program involved self-sampling for human papillomavirus (HPV) DNA testing, followed by teleconsultation with healthcare providers for result interpretation and referral for further management if required. The primary outcome was the participation rate in the telemedicine-based screening program. Secondary outcomes included the positivity rate for high-risk HPV, the rate of referral for colposcopy, and participant satisfaction with the program. Results: A total of 500 women were invited to participate in the study, of whom 380 (76%) completed the screening process. The high-risk HPV positivity rate was 12%, and 46 women (12.1%) were referred for colposcopy. Participant satisfaction with the telemedicine program was high, with 92% of women reporting that they were satisfied with the convenience and accessibility of the service. Conclusion: Telemedicine-based cervical cancer screening is a feasible and effective strategy for reaching women in remote areas of Indonesia. The program achieved a high participation rate and enabled timely referral for further management. This approach has the potential to improve cervical cancer screening coverage and reduce mortality rates in underserved populations.